Reconsidering the Stability of Money Demand in Nigeria - Adebayo, Deborah Bose (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This study attempts to investigate the long run stability of money demand in Nigeria from the period of 1980 to 2018. The data used were sourced from the World Development Indicators (WDI) and the ARDL method of cointegration analysis was used to estimate money demand function. The empirical results provide evidence for the existence of a cointegrating relationship between the real money demand, real GDP, the real deposit interest rate, and financial development. Furthermore, it is shown that financial development plays a key role in the stability of money demand in Nigeria over the long-run.

ÖZ: Bu çalışma, Nijerya'daki para talebinin 1980'den 2018'e kadar olan uzun vadeli istikrarını araştırmaya çalışmaktadır. Kullanılan veriler Dünya Kalkınma Göstergelerinden (WDI) elde edilmiştir ve ARDL eşbütünleşme analizi yöntemi para talebi fonksiyonunu tahmin etmek için kullanılmıştır. Ampirik sonuçlar, reel para talebi, reel GSYİH, reel mevduat faiz oranı ve finansal gelişme arasında eşbütünleşme ilişkisinin varlığına dair kanıt sağlar. Ayrıca, çalışmanın bulguları, finansal gelişmenin Nijerya'daki para talebindeki uzun dönemli istikrarsızlığı anlamada kilit bir rol oynadığını göstermektedir.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Mustafa İsmihan.
Keywords: Economics Department; Economic Conditions and Development--Nigeria; Economic Policy; Money Demand, Financial Development, Nigeria, Cointegration